.Conceptual Framework for Financial Accounting and Reporting: Present and Future (Book). - Burns, Thomas J.; Yu, S.C. (The Accounting Review, 1979)
Abstract Reviews the book "Conceptual Framework for Financial Accounting and Reporting: Present and Future," edited by Joe J. Cramer and Charles A. Neyhart.